(3cTa GdXfhf Yf CSGei GdcJH hGdafhfs - (3eUWaj Hf YHO Gddg GdbSfWjfj GdQhej GdMfaj GdTgjQ HGdedG cGJH GdMdHj, MGLj NdjaIs ((3MSjf Hf eUWai GdMSjfi GdMdHi s)
(3ChdgG (B:s
(3hHYO deG cGf cTa QbGFb GdYdhe hJHjf MbGFbgG ef CLd GdehGgH bGd ajge GdfHi Ydjg GdSdGe (B( (3YdeGA CeJi cCfHjGA Hfi ESQGFjd (B) s
(3BNQgG (B:s
(3bO GfJgi Gdbhd HfG eeG MQQfGg hGdMeO ddg QH GdYGdejf s
(3GdUaMGJ eLOhdI HGdMeQI hGdYfGhjf hCSeGA GdcJH HGdMeQI CjVkGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs